Estudo da remoção de diclofenaco sódico por processo de adsorção - Treméa, Renata (2020)
Population growth combined to technological development has led to a greater demand for everyday chemicals, which ends up affecting water resources. New treatment technologies have been studied to eliminate these compounds present in the water supply. In this sense, under the circumstances of the current Brazilian scenario, this research attempts to find solutions for the presence of these compounds in water supply and the aim of the study is to evaluate the efficiency of the removal of diclofenac sodium in an aqueous solution by the adsorption process using hydrogen titanate nanotubes (H-TiNT) and activated carbon from eucalyptus wood (AC). At the first stage, the experiments were conducted using H-TiNTs. The adsorbent was characterized as the Point of Zero Charge (pHpzc), which resulted in 6.21 and showed an ABET of 309.30 m2 g-1. Adsorption experiments were carried out to evaluate the pH effect and the obtained results showed that the best removal condition occured at pH 2. The kinetic study of diclofenac sodium adsorption in hydrogen titanate nanotubes was evaluated by pseudo-first order, pseudo-second order and intraparticle diffusion models. The kinetic model that best described the adsorption process was the pseudo-first order (R2 = 0.985). The Box-Behnken experimental design was performed to optimize the adsorption process, adopting three parameters: temperature, time and drug concentration. The optimal conditions were 22 °C, 360 min and 14.54 mg L-1. The results demonstrated that it was not possible to observe affinity between hydrogen titanate nanotubes and diclofenac sodium. At the second stage, experiments using the activated carbon were performed. The adsorbent characterization showed a ABET = 619.35 m2 g-1 and a pHpcz = 7.98. The study of the pH effect was conducted measuring different pH values and the best removal was found for the pH of the DCF solution close to the natural (pH = 5). The Box-Behnken experimental design was performed to optimize the adsorption process conditions, adopting three parameters: stirring rate, DCF concentration and adsorbent dosage. The optimal conditions were 183.8 rpm, 15 mg L-1 and 10 mg. The kinetic study was evaluated by pseudo-first order, pseudo-second order and intraparticle diffusion models. The kinetic model that best described the adsorption process was the pseudo-second order (R2 = 0,979). The equilibrium study was evaluated by Langmuir, Freundlich, Sips and RedlichPeterson models. Sips isotherm was the model that best fit the experimental data. For the thermodynamic study, ΔG showed negative values for both temperatures (-28.16, -29.33 and - 30.34kJ mol-1), this implies that the adsorption process was spontaneous and the drug shows high affinity with the adsorbent. The ΔH positive value (3.97 kJ mol-1) indicates that the adsorption process was endothermic and, finally, the ΔS value (0.109 kJ mol-1 K-1) showed that randomness increases at the solid-solution interface during the adsorption process. Thus, due to the activated carbon from eucalyptus wood efficiency in the removal of DCF, this adsorbent is a good alternative for the removal of the drug in aqueous solutions.